PENERAPAN PERENCANAAN PAJAK PENGHASILAN PASAL 21 SEBAGAI STRATEGI PENGHEMATAN PEMBAYARAN PAJAK PADA PT. BARA KUMALA - -, Sintia Faridah (EKONOMIA, 2019)
The purpose of this study is To know Application of Income Tax Planning Article 21 With Gross Up Method Can Save Tax Payment At PT Bara Kumala.The research was conducted by library research that related to the problem that was researched and conducted the research into the field by way of Interview and Direct Observation on PT Bara Kumala. Analyzer used in this research is Tariff of Income Tax Article 21 According to Article 17 of Law no. 36 Year 2008, Concerning Amendment of Non Taxable Income (PTKP) Amount of PTKP Based on Regulation of the Minister of Finance 101 / PMK.010 / 2016, Basis for Imposition of Income Tax Article 21 Pursuant to Regulation of Minister of Finance No. 101 / PMK.010 / 2016, Income Tax Calculation Article 21 Gross method, tax allowance formula with Gross Up Method.After going through the stage of research, analysis and discussion it is known Calculation of Income Tax Article 21 at PT. Bara Kumala, which has 92 employees who already have NPWP and become a taxpayer in the country. PT. Bara Kumala uses the policy with the Gross method in the Calculation of Article 21 Income where employees still bear their own tax payments that have been cut directly from the salary of each employee